2008
DOI: 10.1007/s00464-008-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring and video-assisted thyroidectomy: a prospective, randomized case-control evaluation

Abstract: This is the first VAT series with a standardized IONM technique. The technical feasibility and safety of IONM in selected patients seem acceptable. Neuromonitoring during VAT is effective in providing identification and function of laryngeal nerves. IONM enables surgeons to feel more comfortable with their approach to VAT. A reduction of rates for postoperative complications could not be demonstrated in the present study. Larger series are needed for further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 36 publications
3
89
3
4
Order By: Relevance
“…However, the visual identification rate of EBSLN increased to 68.3% with the aid of IONM, which is close to the rates reported in the studies that included the routine division of strap muscles during superior pole dissection. In this study, the functional identification rate of EBSLN with IONM was noted to be 93.5%, which is threefold of the visual identification rate and in accordance with the rate of 83%-100% reported in other studies (2,8,10,11,15,23). We demonstrated that IONM provided a meaningful contribution to visual (p<0.001) and functional (p<0.001) identification of EBSLN.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the visual identification rate of EBSLN increased to 68.3% with the aid of IONM, which is close to the rates reported in the studies that included the routine division of strap muscles during superior pole dissection. In this study, the functional identification rate of EBSLN with IONM was noted to be 93.5%, which is threefold of the visual identification rate and in accordance with the rate of 83%-100% reported in other studies (2,8,10,11,15,23). We demonstrated that IONM provided a meaningful contribution to visual (p<0.001) and functional (p<0.001) identification of EBSLN.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, 25.2% of all the EBSLNs were identified with IONM, but all of them were not able to be visualized in the present study. In the present study, the visual identification rate of EBSLNs before being stimulated with a probe was only 27.9%, which was lower than the rate of 33%-93% reported in other studies (2,10,11,17,20). In our opinion, the reason for this low rate is that we did not divide the strap muscles to expose the sternothyroid-laryngeal triangle, except only in the patients with enlarged thyroid lobes and a short neck.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Some authors have shown that neuromonitoring can decrease operative time. Nonetheless, the decrease in operative time is around seven minutes, and we believe that this small change does not affect the final conclusions (21). Additionally, we only included direct costs and payer perspective in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is felt that different surgical techniques with different degrees of exposure of the sternothyroid-laryngeal triangle, such as the division of the sternothyroid muscle in Pagedar's series (34), could account for such discrepancy among identification rates (20,24). On the opposite pole of surgical bed exposure, the reports on robotic (72), video-assisted (36), and mini-incision local anesthesia thyroidectomies (37,38) defend that nerve monitoring is feasible and useful in providing, at least, electrophysiological identification of the EBSLN when the field is limited.…”
Section: Intraoperative Ebsln Identification and The Role Of Ionmmentioning
confidence: 99%